(as outras fazedoras de sentidos): imaginaturas e visuaisvivências das artistas de Goiás - Piva, Carolina Brandão (2021)
In this doctoral dissertation, I examine the art practice of fifteen women from the Brazilian state of Goiás whose works I approach from a new methodological perspective, which I poetically call the travel-and-sway look, considered to be a look capable of transforming our ways of seeing contemporary experiences of imagination. Refusing repertoires and categories that lead us to conform our visual approaches to the hegemonies of perception, the travel-and-sway look is built of the exposure to an affective get-through view that allows us to look at the otherness preventing them from being converted into “the exotic” or “the exceptional.” My approach is based on a two-fold movement of defocalization and reparation by which the fifteen women artists who participate in this study, also referred to as “the other visual sense-makers,” are presented. These artists are: Maria Aparecida Pires, Hilda Freire, Socorro Costa, Dete Teixeira, Simône Aguiária, Márcia Malaquias, Emilly Cristina, Madalena Sacramento, Karina Vasconcelos, Maria Selvina Costa, Di Mendonça, Walda Gomes, Nicolly Costa, Neide Guimarães, and Denise Siqueira. They are everyday-life women who have transformed their communities’ ways of seeing and of being seen through art. Their artistic practice is not institutionally legitimated taking place at the crossroads of imagining, imaging, and living, for which reason Brazilian artist Renata Felinto perceives of it as carried out “in the urgency of life.” If we look at these women artists’ crea(c)tions as compositions whose materiality directly reflects on their art practice in relation to the realm of living experience, our reading of these women’s cultural production can set up an approach that expands their relevance as artists beyond the bounds of criticality paving the way for a poethical view, as proposed by Brazilian sociologist and scholar Denise Ferreira da Silva. My attempt in this doctoral dissertation is thus to uncover how art practice’s knowability must result from our interest in approaching it as a social fact that breaks out of the traditional space of art to become a part of ordinary people’s culturimagenativess and visualiving.